Promoting parenting skills among women for increasing pregnancy intention: development of an interventional package - Najmeh Tehranian; Katayoun Jalali-Aria; Eesa Mohammadi; Anoshirvan Kazemnejad (Payesh)
Objective(s): Reduction of the fertility rate is one of the most critical concerns of policymakers in Iran. Women expressed concerns about the feeling of incompetence in raising children. This study was conducted to provide an intervention program of parenting skills training based on the theory of planned behaviour to increase pregnancy intention. Methods: Through a qualitative study on barriers to childbearing, feelings of inadequacy were identified as an important factor in preventing women to have a child. After searching reliable sites, the educational intervention program on the art of parenting was compiled based on the theory of planned behaviour, with the content of self-awareness skills, the art of parenting by UNICEF, and the Islamic thoughts. Qualitative content validity was used to validate the program. For this purpose, the program was sent to 10 experts. The program consisted of 6 sessions; at the end of each session, there was an evaluation form. After collecting opinions and modifying the program, it was reviewed for final approval. Results: In this 6-session program, goals, educational strategy and educational content have been developed for each session. The program has been written in a way that teachers can implement the program easily. The program was planned for use by single, married, childless or childbearing women. Conclusion: Health service providers can use this program to educate women and increase their sense of empowerment to facilitate pregnancy.